Green finance and information technology: contradictions and cooperation - A. N. Zhilkina; O. N. Zhilkin; E. P. Bondarovich (Вестник университета, 2022)
Changing priorities in understanding the drivers of sustainable growth of the global and national economy has led to the emergence and rapid development of green finance with the active support of new information technologies. The article is devoted to the negative and positive impact of information technology on the need for green finance, their development and growing popularity among investors. The latest indicators on harmful emissions into the atmosphere are quite alarming, even modern artificial intelligence technologies, due to their high energy intensity, negatively affect the health of our planet. The study is based on the use of comparison methods, absolute and relative indicators, deduction and induction, value and physical indicators. One of the conclusions of the work is that information technology helps investors make the right decisions on investing in an innovative green economy, green bonds are considered in detail as the main, reliable tool for green finance.